COVID-19 ja udmurdi pärimuskultuur - Nikolai Anisimov; Galina Glukhova (Mäetagused, 2020)
In this article, we examine the spring ceremonies, the Eastern Udmurt’s summer ceremonies, and the Udmurt holidays (the Great Day, the Day of the Plough, Easter, commemoration days, etc.) during the COVID-19 quarantine as well as the humorous songs and chastushkas inspired by the quarantine and self-isolation. This article is the first attempt to describe and characterise the influence of the pandemic on the example of the Udmurt traditional culture. In our analysis, we rely on internet posts, data transmitted by informants, articles in district papers as well as observations by the authors. The data allow us to evaluate the changes in Udmurt customs and people’s adaptation to critical situations. Self-isolation caused anxiety in many village dwellers, because it was not possible to party in real time and place. The internet posts confirmed that the Udmurt are happy to share preparations and proceedings of their feasts, they like to send congratulations to friends and kin, who are able to participate both in joyful and sad emotions. The humorous Udmurt songs and chastushkas posted on the Internet help to survive in the difficult situation in the republic due to the COVID-19 crisis.